Nanostructured Spinel Manganates and Their Composites for Electrochemical Energy Conversion and Storage - Rani, Balasubramanian Jansi; Sivanantham, Arumugam; Cho, In Sun (Advanced Functional Materials, 2023)
Spinel manganates (AMn2O4; A = Co, Ni, Cu, Zn, and Fe; collectively referred to as AMO) are promising electrode materials for water electrolyzers, pseudocapacitors, and batteries owing to their inherent advantages such as valence variability, high catalytic activity, conductivity, stability, low-cost, and environmental friendliness. Nanostructured materials, with a large surface area and short ion diffusion length, offer great potential for achieving enhanced electrochemical performance. This review summarizes spinel manganates with various nanostructured morphologies and discusses the impact of the structure and composition on the electrochemical performance. The review demonstrates that nanostructured spinel manganates with preferred A-site cation significantly improve the thermodynamics and electrochemical reaction kinetics at solid–liquid and solid–solid interfaces. Notably, faceted, hollow, 1D nanostructured CoMn2O4 and its nanocomposites (CoMn/CoMn2O4 and NiMn2O4/C) exhibit outstanding electrochemical performance. The review also provides an overview of the importance of energy conversion and storage, and the advantages of spinel manganates as electrode materials. Additionally, the review describes feasible methods of synthesizing AMO nanostructures and nanocomposites. The insights provided in this review are expected to contribute to the synthesis of spinel manganates with desired morphologies and compositions, enabling the future development of efficient electrode materials for energy conversion and storage devices.
Keywords: Electrochemical energy conversions; Electrochemical energy storage; Electrochemical performance; Electrode material; Electrolyzers; Energy conversion and storages; Nano-structured; Pseudocapacitors; Spinel manganate; Synthesis method; electrochemical performance; nanocomposites; nanostructures; spinel manganates; synthesis methods